Cloning and expression of Toxoplasma gondii dense granular protein 4 (GRA4) in Pichia pastoris - Lau, Y.L.; Hasan, M.T.; Thiruvengadam, G.; Idris, M.M.; Init, I. (2010)
GRA4 of Toxoplasma gondii has been shown to prompt IgG, IgM and IgA responses in previous studies and is thus considered one of the major immunogenic proteins from T. gondii that can be used for both diagnostics purposes and vaccine development. This study seeks to clone and express the GRA4 in Pichia pastoris, which has numerous advantages over other systems for expression of eukaryotic proteins. In order to achieve this, the gene was cloned into the pPICZ alpha A expression vector, which was then incorporated into the P. pastoris genome via insertional integration for expression of the recombinant protein, under the AOX1 promoter. The antigen was expressed along with the prepro sequence of the alpha-factor of yeast so that it could be excreted out of the P pastoris cells and obtained from the medium. Upon SDS-PAGE analysis it was found that the recombinant protein was expressed optimally as a 40 kDa protein after 96 hours of induction with 0.75 of methanol. The expressed GRA4 protein showed discrepancy in size with the calculated molecular mass. This may be attributed to the various posttranslational modifications including glycosylation and phosphorylation. Despite the difference in molecular weight, the recombinant protein was able to detect toxoplasmosis in Western blot format. The recombinant GRA4 was expressed with an intact polyhistidine-tag, which could be used for future purification of the antigen.